Senility and youth as still actual, versatile literary and cultural motifs — an introduction to the collection of studies - Kuran, Michał; Agnieszka Gralak (Starość i młodość w literaturze i kulturze, 2016)
The study presents selected examples of functioning in the literature and culture the category of senilityand youth in the idea of Antiquity, as well as examples from the circle of literature of Renaissance andBaroque (in the context especially of Parenetics). The versatility of these categories present also proverbsexisting in such works of culture as Erazm of Rotterdam’s Adagia and Ezop’s fables. The examples ofmeetings, but also confrontations, and well as independent functioning motifs of senility and youth inthe art are among others paintings of Teodor Axentowicz and Wlastimil Hofman. The study also paysattention to the transformations, which have occurred in the functioning of senility and youth in theculture of recent years, including changes in defining their borders. Deliberations present afterwardscourse of conference devoted to the titled issue and also they describe motifs, which have guided to groupstudies collected in the volume.